2009
DOI: 10.1182/blood-2009-07-233718
|View full text |Cite
|
Sign up to set email alerts
|

Diverse marrow stromal cells protect CLL cells from spontaneous and drug-induced apoptosis: development of a reliable and reproducible system to assess stromal cell adhesion-mediated drug resistance

Abstract: IntroductionWith the establishment of more effective treatments for patients with chronic lymphocytic leukemia (CLL) over the past decade, complete remissions are no longer the exception. 1 Despite these major improvements in CLL treatment, we still consider CLL an incurable disease, because patients generally relapse from minimal residual disease (MRD). 2 There is growing evidence suggesting that CLL cells are protected from conventional drugs in tissue microenvironments, such as the bone marrow and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
283
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(308 citation statements)
references
References 61 publications
(61 reference statements)
25
283
0
Order By: Relevance
“…41,42 Previous studies to model the in vivo marrow microenvironment employed co-culture assays with various BMSC of murine 6,43 and human 11,44 origins, and we recently demonstrated that murine and human BMSC do not significantly differ in their capacity to support CLL cell viability, protection from cytotoxic drugs and maintenance of antiapoptotic proteins, such as MCL1. 12 We previously reported that BMSC induce activation and/or increased expression of molecules involved in CLL survival, such as MCL1. 45 This study, however, is the first to systematically analyze GE changes induced by BMSC, and to uncover BMSC-induced TCL1 expression.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…41,42 Previous studies to model the in vivo marrow microenvironment employed co-culture assays with various BMSC of murine 6,43 and human 11,44 origins, and we recently demonstrated that murine and human BMSC do not significantly differ in their capacity to support CLL cell viability, protection from cytotoxic drugs and maintenance of antiapoptotic proteins, such as MCL1. 12 We previously reported that BMSC induce activation and/or increased expression of molecules involved in CLL survival, such as MCL1. 45 This study, however, is the first to systematically analyze GE changes induced by BMSC, and to uncover BMSC-induced TCL1 expression.…”
Section: Discussionmentioning
confidence: 98%
“…The bone marrow stroma cell (BMSC) lines KUSA-H1 (murine) and StromaNKtert (human) 23 were purchased from RIKEN (Ibaraki, Japan) and cultured as described. 12 CLL cell viability was studied by the analysis of mitochondrial transmembrane potential using 3,3 0 -dihexyloxacarbocyanine iodide (DioC6; Molecular Probes, Life Technologies, Grand Island, NY, USA) and by cell membrane permeability to propidium iodide (SigmaAldrich, St Louis, MO, USA), and measured by FACSCalibur flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Cell Purification and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…SDF-1-CXCR4 and VCAM-1-VLA-4 interactions, delivering a major part of cell-adhesion-based protection to CLL cells, are highly conserved between the human and murine system, and thus CLL cell co-culture with murine M2-10B4 has been shown to be a reliable in vitro model to study complex microenvironmental interactions. 31,32 The viability of fludarabine-treated CLL cells was enhanced by co-culturing with M2-10B4 (from 52 ± 23% to 83±38%; P40.001). In contrast, the viability after actinomycin D treatment was similar in the absence (26±21%) or presence (25 ± 22%) of M2-10B4 stromal cells (P ¼ 0.367, Figure 2b).…”
Section: Identification Of P53-independent Apoptosis Inducersmentioning
confidence: 99%
“…The dependence of leukemic Bcells on microenvironment signals is further highlighted by the observation that despite their prolonged survival in vivo [2], they undergo spontaneous apoptosis when cultured ex vivo [2]. Interestingly, a variety of stromal cell lines have been shown to enhance the survival of CLL cells in co-culture experiments [3][4][5][6][7][8][9][10] and even protect them from drug-induced apoptosis [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%